A case report of vaccine-induced immune thrombotic thrombocytopenia (VITT) with genetic analysis - Mendes-de-Almeida, Daniela P.; Kehdy, Fernanda S. G.; Martins-Gonçalves, Remy; Bokel, Joanna; Grinsztejn, Eduarda; Mouta Nunes de Oliveira, Patrícia; Maia, Maria de Lourdes de Sousa; Hoagland, Brenda; Wagner Cardoso, Sandra; Grinsztejn, Beatriz; Siqueira, Marilda M.; Kurtz, Pedro; et al. (Frontiers in Cardiovascular Medicine, 2023)
The emergence of the rare syndrome called vaccine-induced immune thrombocytopenia and thrombosis (VITT) after adenoviral vector vaccines, including ChAdOx1 nCov-19, raises concern about one's predisposing risk factors. Here we report the case of a 56-year-old white man who developed VITT leading to death within 9 days of symptom onset. He presented with superior sagittal sinus thrombosis, right frontal intraparenchymal hematoma, frontoparietal subarachnoid and massive ventricular hemorrhage, and right lower extremity arterial and venous thrombosis. His laboratory results showed elevated D-dimer, C-reactive protein, tissue factor, P-selectin (CD62p), and positive anti-platelet factor 4. The patient's plasma promoted higher CD62p expression in healthy donors' platelets than the controls. Genetic investigation on coagulation, thrombophilia, inflammation, and type I interferon-related genes was performed. From rare variants in European or African genomic databases, 68 single-nucleotide polymorphisms (SNPs) in one allele and 11 in two alleles from common SNPs were found in the patient genome. This report highlights the possible relationship between VITT and genetic variants. Additional investigations regarding the genetic predisposition of VITT are needed.